RAT BLOOD PROFILE EVALUATION AFTER Fe3O4/CHITOSAN COLLOID INJECTION - Aloma Karo Karo; Irham Abdul Azis; Wildan Z.L.; Grace Tj. Sulungbudi; Berry Juliandi; Mujamilah Mujamilah (Jurnal Sains Materi Indonesia, 2019)
RAT BLOOD PROFILE EVALUATION AFTER Fe3O4/CHITOSAN COLLOID INJECTION. The application of iron oxide (Fe3O4) magnetic nanoparticles in the biomedical field is still being explored, mainly related to its toxicity and side effects. This article reported results of the study aimed at analyzing the effect of chitosan-coated magnetic nanoparticles (NPM-C) on rat blood profiles. Magnetic colloid as much as 1 ml (concentration of 5 mg NPM-C / mL aquabidest) for 1 kG rat body weight was injected through intra-venous to the treated rat group (4 Wistar rats aged 6 months; weight ± 275 grams; male sex) while another four rats injected with sterile aquabidest used as a control group. The blood taking from each group of rats was carried out on 1 day before injection and several days after injection (days 1, 7, 14, 21, 28) through veins in the tail. To these blood samples, a series of blood profile analyzes is carried out including basic hematology, blood chemistry, and fragility of the erythrocyte membrane. The results of the analysis showed no significant differences between blood profiles after treatment and control, which indicated that chitosan-coated magnetic nanoparticles did not trigger cellular stress responses in the blood. The stability of blood magnetism analyzed by VSM (Vibrating Sample Magnetometer) also shows that magnetic nanoparticles are detected in the blood and tend to decrease in number with increasing time, so it is thought that these nanoparticles can be degraded or have been distributed into organs. These stable properties are analyzed due to an existence of chitosan coating around magnetic nanoparticles. Based on this study it can be concluded that up to the given concentration limit, iron oxide nanoparticles coated by chitosan are not toxic and have the potential to be used as drug carriers, MRI contrast agents, and other biomedical applications.